Use of the Suicide Status Form-II to investigate correlates of suicide risk factors in psychiatrically hospitalized children and adolescents - Romanowicz, Magdalena (2013)
BACKGROUND: Suicide is the third leading cause of death in the United States for youth 12–17 years or age. Acute psychiatric hospitalization represents a clear worst point clinically and acute suicide risk is the most common reason for psychiatric admission. We sought to determine factors associated with differences in individual suicide risk assessment for children and adolescents during acute psychiatric admission. METHODS: Study participants were 1,153 youth consecutively admitted to an inpatient psychiatry unit who completed a self-administered Suicide Status Form (SSF) within 24 hours of admission. Additional information on suicide risk factors was obtained through medical chart abstraction. RESULTS: Females reported significantly greater psychological pain, stress, hopelessness, and self-hate on the SSF and were significantly more likely to have made a suicide attempt just prior to the index hospital admission (OR = 1.59, SE = .29; CI = 1.12–2.26), report a family history of suicide (OR = 2.02, SE = .33; CI = 1.47–2.78), and had experienced a greater number of inpatient psychiatry admissions related to suicidal ideation (RR = 1.33, SE = .13; CI = 1.10–1.61). High school aged youth and those with a primary diagnosis of depression displayed consistently elevated SSF scores and risk factors for suicide compared to comparison groups. LIMITATIONS: Diagnosis was determined through chart abstraction. Responses to access to firearm question had missing data for 46% of the total sample. CONCLUSIONS: Systematic administration of a suicide-specific measure at admission may help clinicians improve identification of suicide risk factors in youth in inpatient psychiatry settings.